Certificate-based strategy to auction model for e-procurement in Indonesia: a review on local ethics and the future challenges - Nanang, Herlino; Misman, Ahmad Fatzilah (The Institute of Electrical and Electronics Engineers, Inc., 2016)
This paper is intended to review the literature review relating to the implementation of e-procurement in Indonesia generally and in local government in particular. From some literature review undertaken, the author found that there is a lack of implementation of e-procurement, as there are loopholes that allow for decision makers winner of the auction and bidders. Because it contains only replacing the system of a conventional system to an electronic-based system. Based on data from corruption eradication commission in 2015, showed that 70% of the cases of corruption in Indonesia is from government procurement. Therefore, the authors propose that the conduct of the auction-based electronic government procurement must use certificates with the aim of users authorize the use of public key and only the person entitled to be able to access.